The Reflective-Accommodative Approach to the Quran: Ahmad Syafii Maarif’s Contribution towards Contemporary Approach to the Quran` - Muhammad K Ridwan (Universitas Islam Negeri Mataram, 2021)
This paper aims to examine Ahmad Syafii Maarif’s inclusive thought and reveal the epistemological basis of interpreting the Qur’an. It further explores to what extent Maarif’s thought has contributed to the development of contemporary Quranic studies. Although Maarif is not an expert of Quranic commentator (mufassir) and does not author works related to the Qur’an, he is well-known as an inclusive-pluralist Muslim scholar who is concerned with promoting the moral-ethical values of the Qur’an. In formulating the ideas of the Quranic epistemology, Maarif consistently embarks from an in-depth exploration of historical knowledge and then refers to the Qur’an to examine a contemporary reality. This approach was connected by forming the world-view of the Qur’an in order to propose the spirit of moral ethics and the principle of justice as a theological lens which he then use to generate creative-alternative solutions dealing with the nation’s problems through a process of contextualization. Maarif’s Quranic epistemology affirms his project to achieve an idealistic Islam, namely the realization of a Muslim community that is consistently guided by the spirit of the moral ethics of the Qur’an.